Transcriptome expression profiling in response to drought stress in Ilex paraguariensis leaves - Acevedo, Raúl Maximiliano (2016)
Ilex paraguariensis St. Hil. is recognized as a shade-tolerant tree, cultivated in north-eastern Argentina, south-eastern Brazil, and Paraguay. Its leaves and young shoots are industrialised and; hence, being used to prepare a traditional tea-like infusion (mate-tea) with various medicinal benefits. Under the prevailing agro-climatic conditions in NE Argentina and with the occurrence of high temperatures and scarce rains during spring or summer, I. paraguariensis plants are subjected to water stress, reducing their yield. Differential Display was used to compare differences in gene expression between stressed and unstressed (control) potted plants. We found 52 differentially expressed transcripts (DETs), analysing banding patterns of Differential Display polyacrylamide gels, in which 38 DETs were induced, and 14 DETs were repressed in response to drought. Sequence comparisons revealed that 19% of the fragments showed no homologies, whereas 40.5 % of the total number of fragments had strong similarities with database entries of known functions. The other DETs belonged to unclassified proteins or genes with unknown functions. Interestingly, 12% of the DNA sequences were related to signal transduction, and 2% of the sequences were identified as transcription factors. Approximately, 12% of the annotated sequences were involved in stress tolerance and metal homeostasis, while 7% of the DETs were associated with photosynthesis. Other groups, representing 12%, included those involved in secondary metabolism, lignin biosynthesis, cell walls and RNA stabilization/chaperone activity. When integrated with physiological data, our results suggest that the transcriptional activity of some of the studied genes could be related to the degree of drought tolerance/susceptibility of I. paraguariensis.